Lecturer at seminar for PhD students: Title: From the quarry to the building: Pathologies, chemical and physical decay of building stones materials used in ancient and contemporary architecture - Sitzia, Fabio (2022)
From the quarry to the building: pathologies, chemical and physical decay of building stones materials used in ancient and contemporary architecture